The position of confirmed pre-main sequence pulsators in the H-R diagram and an overview of their properties. Issue Volume 9:Issue S301(2013) (18th February 2014) - Zwintz, Konstanze; Casey, Mike; Guenther, David
Abstract: Pre-main sequence (PMS) stars can become vibrationally unstable during their evolution to the zero-age main sequence (ZAMS). As they gain their energy from gravitational contraction and have not started nuclear fusion in their cores yet, their inner structures are significantly different to those of (post-) main sequence stars and can be probed by asteroseismology. Using photometric time series from ground and from space ( MOST, CoRoT & Spitzer ) the number of confirmed pulsating pre-main sequence stars has increased significantly within the last years and allowed to find members of new classes of PMS pulsators. Apart from the well-established group of δ Scuti type PMS stars, members of the groups of PMS γ Doradus, PMS δ Scuti – γ Doradus hybrid and PMS slowly pulsating B (SPB) stars have been discovered. For five PMS δ Scuti candidates, space photometry has revealed that they only show irregular variability, but no pulsations. The unique high-precision space data were combined with dedicated high-resolution spectra to probe the parameter space in the H-R diagram and study the properties of PMS pulsators in comparison to their evolutionary stage.